2012
DOI: 10.1039/c2cc36341k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed mono- and double-carbonylation of indoles with amines controllably leading to amides and α-ketoamides

Abstract: A novel and efficient double-carbonylation of indoles with primary or secondary amines to yield indole-3-α-ketoamides has been developed and bioactive molecules could be one-pot synthesized using the current methodology, which could also be selectively switched to mono-carbonylation to afford indole-3-amides only by a slight modification of reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…Traditional nucleophilic acyl substitution reactions are a well‐known synthetic strategy for these compounds, though these methods need a pre‐installed carbonyl moiety in the amine or indole skeleton [Scheme , Equation (1) and Equation (2)] . Aminocarbonylation of indole with carbon monoxide and amines via the generation of the 3‐iodoindole intermediate in the presence of a palladium catalyst and iodine have also been reported [Equation (3)] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional nucleophilic acyl substitution reactions are a well‐known synthetic strategy for these compounds, though these methods need a pre‐installed carbonyl moiety in the amine or indole skeleton [Scheme , Equation (1) and Equation (2)] . Aminocarbonylation of indole with carbon monoxide and amines via the generation of the 3‐iodoindole intermediate in the presence of a palladium catalyst and iodine have also been reported [Equation (3)] …”
Section: Introductionmentioning
confidence: 99%
“…[5] Aminocarbonylation of indole with carbon monoxide and amines via the generation of the 3-iodoindole intermediate in the presence of a palladium catalyst and iodine have also been reported [Equation (3)]. [6] Scheme 1. Strategy for the synthesis of indole-3-carboxamides.…”
Section: Introductionmentioning
confidence: 99%
“…通过芳基甲基酮 [11] 、芳基乙 炔 [12] 、芳基乙烯 [13] 、芳基乙烷 [14] 、α-羰基醛 [15] 、芳基乙 醛 [16] 的氧化酰胺化也是一类常用的方法. 另外芳基 碘 [17] 或吲哚 [18] 的双羰化酰胺化也可构建 α-酮酰胺衍生 物. 近年来, 炔酰胺的氧化已经成为构建 α-酮酰胺的重 要方法.…”
unclassified
“…However, only rare methods have successfully synthesized 3-diketoindoles. [9][10][11][12][13][14] Traditional Friedel-Crafts acylation between indoles and oxalyl chloride achieved the synthesis of 3-diketoindoles but suffered f r o m p o o r s e l e c t i v i t y a n d l o w y i e l d ( S c h e m e 1 a ) . 9 35 Glyoxylation/Stephens-Castro coupling sequence reported by…”
mentioning
confidence: 99%
“…A further screening of the solvents revealed that the reaction yield was strongly influenced by the solvent used, and toluene was demonstrated to be the best choice for this transformation (entries 70[10][11][12][13][14].…”
mentioning
confidence: 99%